Risk of Mortality Caused by Silicosis and Lung Cancer: a Study on Ceramic Tile Factory Workers - Nourmohammadi, Mohammad; Fallah Asadi, Ayda; Mosavi Jarrahi, Alireza; Yari, Saeed (Asian Pacific Journal of Environment and Cancer, 2018)
Exposure to silica dust may be considered as an important hazard in the tile industry. The aim of this research was to determine workers’ exposure to crystalline silica dust and assess the relative risk of silicosis and the excess lifetime risk of mortality from lung cancer in tile industry. The visible spectroscopy, based on the NIOSH method 7601, was employed to the do sampling and analysis. For estimate the rate of silicosis relate mortality and the excess lifetime risk of mortality from lung cancer the Mannetje and rice model used. The highest average of the exposure rate to silica were in Stone crusher (0/43 mg/m3) section and press section while the lowest average of the exposure rate to free silica was in packaging section (0/12 mg/m3). 95 percent of the study samples scored above the occupational exposure limit0.05 mg/m3NIOSH standard.